2017
DOI: 10.1155/2017/3457614
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin-Guided Antibiotics after Surgery for Peritonitis: A Randomized Controlled Study

Abstract: Background Serum procalcitonin (PCT) is a useful biomarker to tailor the duration of antibiotics in respiratory infections. The objective of this study was to determine whether PCT levels could tailor postoperative antibiotic therapy in patients operated for peritonitis. Method Patients with peritonitis were randomized postoperatively. The control group received antibiotics for a defined duration according to institutional guidelines. In the study group, antibiotics were stopped based on serum PCT levels. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
11
1
2
Order By: Relevance
“…Our findings indicate a significant difference in the duration of antibiotic delivery between the study group and the control group, with a reduction in the duration of antibiotic delivery to patients of the study group by 2.6 days without risking a recurrence of infection. Our findings do not correspond to the study conducted by Juliette [ 21 ], which states that in general there is no significant difference in the duration of antibiotic delivery between the study group and the control group. They revealed the difference by structure of pathogenesis of infections, concluding that there is a difference in the duration of antibiotic delivery between groups of patients with peritonitis due to gastrointestinal perforation (7 days in the PCT and 10-days with control group for p = 0.065), while in patients with localized peritonitis and postoperative peritonitis caused by intestinal dehiscences, there was no reduction of antibiotics with PCT algorithm.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings indicate a significant difference in the duration of antibiotic delivery between the study group and the control group, with a reduction in the duration of antibiotic delivery to patients of the study group by 2.6 days without risking a recurrence of infection. Our findings do not correspond to the study conducted by Juliette [ 21 ], which states that in general there is no significant difference in the duration of antibiotic delivery between the study group and the control group. They revealed the difference by structure of pathogenesis of infections, concluding that there is a difference in the duration of antibiotic delivery between groups of patients with peritonitis due to gastrointestinal perforation (7 days in the PCT and 10-days with control group for p = 0.065), while in patients with localized peritonitis and postoperative peritonitis caused by intestinal dehiscences, there was no reduction of antibiotics with PCT algorithm.…”
Section: Discussioncontrasting
confidence: 99%
“…The restraints of the values measured by this method are from 0.02 to 100 ng/mL. Values below the detectable limit are reported as < 0.02 ng/mL, whereas those over the upper limit are reported >100 ng/mL [ 21 ]. PCT values in healthy people are low <0.1ng/mL [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data from a recent meta-analysis also indicated that PCT-guided antimicrobial treatment in the intensive care unit decreased mortality, including the subgroup of individuals with intra-abdominal infection, although this subgroup did not have a decrease in the length of antimicrobial duration compared to other sites of infection [39]. Conversely, a randomized controlled study that evaluated PCT levels to guide postoperative antimicrobial therapy in patients with peritonitis did not find significant differences in the duration of antimicrobials in the group with PCT guidance compared to the group that received standard treatment [40]. However, this study included a broad range of underlying etiologies and was not powered for subgroup analysis which could explain the lack of statistical significance in the group with peritonitis secondary to gastrointestinal perforation.…”
Section: Discussionmentioning
confidence: 87%
“…Probably this was secondary to low adherence to the protocol and also because a high rate of patients in whom bacterial infection would not be suspected using clinical signs were included, thereby underestimating the usefulness of PCT-guided protocols in pathologies with which physicians would use antibiotics more consistently. In surgery patients, some authors have demonstrated the usefulness of PCT guided protocols, as in peritonitis cases, with a 50% reduction in antibiotic duration [32]. There are no data in adults about the use of a PCT-guided protocol in patients after CVS.…”
Section: Discussionmentioning
confidence: 99%